Augmenting protein-rich biomass from desert vegetable waste: Effects of various fermentation parameters - Nur Fathin, Ruslan; Noormazlinah, Ahmad; Sanfilippo, Antonio; Ali, Muhammad Qasim; Mimi Sakinah, Abdul Munaim; Nour, Abdurahman Hamid (Springer, 2025)
The accumulation of vegetable waste from agriculture, especially in desert regions, poses significant environmental challenges and represents untapped potential for resource utilization. To address this, we investigated a sustainable solution for converting desert vegetable waste into valuable protein through solid-state fermentation (SSF). This study used Rhizopus oligosporus to transform vegetable waste into protein-rich biomass, optimizing critical parameters like incubation temperature, time, inoculum size, and wheat bran addition through a single-variable-at-a-time (SVAT) approach. The results revealed a maximum protein yield of 1049.59 µg/mL under optimal conditions: 40 °C for 2.5 days, 3.6% (w/w) inoculum size, and 50% (w/w) wheat bran. This represents a 4.3-fold increase in protein yield, or a 329.72% improvement compared to unfermented waste. Our findings underscore the potential of SSF as an effective method for valorizing desert agricultural waste, contributing to enhanced food security and reduced environmental impact in arid regions.